Обобщения теоремы Кигурадзе о корректности линейных краевых задач - Михайлец, В.А.; Рева, Н.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The dependence of a continuous parameter in linear boundary-value problems for systems of differential equations is studied. Two generalizations of Kiguradgze’s theorem are established.